The Entrepreneurship Training and Housewives’ Economic Independence: The Strategic Role of MSMEs and Socio-Economic Moderators - Kasmo, Arief Bowo Prayoga; Riyanto, Setyo; Sukardiman, Diah Fistiani; Suparno, Joko (Management Institute Faculty of Economics Universitas Andalas, 2025)
Entrepreneurship training has been widely recognized as an effective strategy to enhance the economic empowerment of housewives, particularly in the context of Micro, Small, and Medium Enterprises (MSMEs). This study aims to examine the effect of entrepreneurship training on the economic independence of housewives, with MSME strategies as a mediating variable and socio-economic factors as a moderating variable. The research sample consisted of 133 housewives engaged in MSMEs and residing in Kembangan District. A quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed to analyze both direct and indirect relationships among the variables. The results indicate that entrepreneurship training does not have a direct effect on economic independence. However, it significantly influences MSME strategies, which subsequently contribute positively to economic independence. This confirms the role of MSME strategies as an important mediator linking entrepreneurship training to economic outcomes. In addition, socio-economic factors were found to have a direct effect on economic independence, but they did not function effectively as moderating variables. These findings underscore that entrepreneurship training alone is insufficient to economically empower housewives. Its effectiveness depends on the implementation of appropriate MSME strategies. The study highlights the importance of strengthening MSME development as a strategic pathway to enhance the economic independence of housewives, while recognizing socio-economic conditions as direct determinants rather than moderating influences.